Pelatihan Pengelolaan dan Pemusnahan Limbah Obat Rusak dan Kadaluarsa di Desa Kotapulu Kabupaten Sigi - Tandah, Muhamad Rinaldhi; Diana, Khusnul; Adisaputra, Arya Dibyo; Hardani, Ririen (JURNAL PENGABDIAN FARMASI DAN SAINS, 2024)
The widespread circulation of illegal drugs poses a serious threat to society as it can have negative impacts on health. In 2019, BPOM Palu confiscated illegal drugs and cosmetics from various areas in Central Sulawesi. A law enforcement operation in Sigi Regency on September 23, 2020, together with the Central Sulawesi Regional Police, successfully seized Class G prescription drugs, traditional medicines, and illegal cosmetics (BPOM Palu, 2022). The main cause of illegal drug circulation is the improper reuse of household drug waste, exploited by irresponsible parties. The use of illegal drugs, which may consist of counterfeit, damaged, or expired items, can endanger health and even lives. One crucial step to prevent this is by managing drug waste properly. Since 2019, BPOM has been conducting awareness campaigns such as "Beware of Illegal Drugs, Dispose of Drug Waste Properly" to educate the public on proper drug disposal (BPOM, 2019). Many people still don't understand the correct way to manage and dispose of expired drugs. Most of them throw these drugs into the trash, potentially fueling illegal drug reuse by irresponsible parties. Training and awareness efforts, such as those conducted in Kotapulu Village, Dolo District, Sigi Regency, are highly relevant. With better knowledge of proper drug management and disposal, it is hoped that communities can independently address drug waste issues, ultimately reducing the circulation of illegal drugs in the region. These activities are crucial for educating the public about the dangers of illegal drugs and the importance of proper drug waste management. The goal is to help reduce the circulation of illegal drugs, especially in Central Sulawesi, thereby safeguarding the overall health and safety of the community.